Stability of mean values: Application of the bates method to field hockey - Penn, M.; Ball, K.; Farrow, D. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
A limitation within biomechanics research is an insufficient number of trials are analysed. Conjecture exists over the minimum number of trials required to achieve a stable mean. This study was conducted to identify the minimum number of trials necessary for mean values of selected kinematic variables to stabilise, using the progressive standard deviation method adapted from Bates et al. (1983). Three-dimensional kinematic data of the field hockey hit was collected using a 10-camera Vicon motion analysis system and analysed using Visual 3D (C-Motion). Mean values for selected parameters were calculated and the progressive change in standard deviation assessed. Results showed the number of trials needed for mean stabilisation is both parameter and task specific. The last threshold approach should be used to account for variability within parameters.